Interventions in overcrowding of emergency departments: an overview of systematic reviews - Bittencourt, Roberto José; Stevanato, Angelo de Medeiros; Bragança, Carolina Thomé N. M.; Gottems, Leila Bernarda Donato; O’Dwyer, Gisele (Revista de Saúde Pública, 2020)
OBJECTIVE: To present an overview of systematic reviews on throughput interventions to solve the overcrowding of emergency departments. METHODS: Electronic searches for reviews published between 2007 and 2018 were made on PubMed, Cochrane Library, EMBASE, Health Systems Evidence, CINAHL, SciELO, LILACS, Google Scholar and the CAPES periodicals portal. Data of the included studies was extracted into a pre-formatted sheet and their methodological quality was assessed using AMSTAR 2 tool. Eventually, 15 systematic reviews were included for the narrative synthesis. RESULTS: The interventions were grouped into four categories: (1) strengthening of the triage service; (2) strengthening of the ED’s team; (3) creation of new care zones; (4) change in ED’s work processes. All studies observed positive effect on patient’s length of stay, expect for one, which had positive effect on other indicators. According to AMSTAR 2 criteria, eight revisions were considered of high or moderate methodological quality and seven, low or critically low quality. There was a clear improvement in the quality of the studies, with an improvement in focus and methodology after two decades of systematic studies on the subject. CONCLUSIONS: Despite some limitations, the evidence presented on this overview can be considered the cutting edge of current scientific knowledge on the topic.